Фортеця на ім'я жінка у пісенному фольклорі слов'ян - Конєва, Я. (Народна творчість та етнографія, 2006)
Folkloric culture reconstructs person's existence as the modality of the relations of female (inner) and male (outer) origins. Folkloric images of the virgin, woman, mother or witch are interconnected with the surrounding space - a house, town, field or a coffin, which are different dimensions of the universal space. Folkloric texts contain almost every version of the woman-space; and each symbol has its own motives and plots.